Mitigating Paxlovid™-induced drug‒drug interaction toxicity: an in silico insight - Ta, Giang H.; Leong, Max K. (Frontiers in Pharmacology, 2024)
The clinical drug-drug interaction side-effects of Ritonavir, an ingredient in Paxlovid™, have been documented, highlighting the need to explore alternative administration methods for Nirmatrelvir, another drug in the Paxlovid™ combination. In this study, the skin permeability potential of Nirmatrelvir was assessed using various in silico models. The prediction results suggest that Nirmatrelvir could be administrated via the transdermal route, offering a promising avenue to enhance the efficacy of anti-COVID-19 agents.